2018
DOI: 10.1155/2018/1381864
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Ripening Evaluation of Ewes’ Cheeses by Fourier-Transformed Infrared Spectroscopy under Real Industrial Conditions

Abstract: The ripening changes over time of special cheeses (Pecorino, ewes’ ripe, and Gouda) made with ewes’ milk were evaluated using FTIR/ATR spectroscopy during approximately one year. The midinfrared FTIR/ATR analyses were carried out in different ripening times between the cheese varieties and processed by means of multivariate statistical approaches. Overall, during the maturation, we observed a downward trend of the absorbance intensity of the amide group peaks (1700 to 1500 cm−1), which is linked to the breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The two peaks that are very clearly visible are suitable for amide I (C=O, C-N), with a wavelength of about 1650 cm −1 , and for amide II (N-H, C-N), with a wavelength of about 1550 cm −1 , as shown by the interpretation of the bean spectra. Additionally, the second peak recorded is due to the peptide (CO-NH) bond [ 76 , 77 ]. Thus, it can be concluded that the peaks in the range of 1700–1500 cm −1 are due to the vibrations produced by the peptide bonds and thus they can be an indicator for the protein content of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…The two peaks that are very clearly visible are suitable for amide I (C=O, C-N), with a wavelength of about 1650 cm −1 , and for amide II (N-H, C-N), with a wavelength of about 1550 cm −1 , as shown by the interpretation of the bean spectra. Additionally, the second peak recorded is due to the peptide (CO-NH) bond [ 76 , 77 ]. Thus, it can be concluded that the peaks in the range of 1700–1500 cm −1 are due to the vibrations produced by the peptide bonds and thus they can be an indicator for the protein content of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Cheese ripening is a complex process in which three flavor generating pathways, glycolysis, lipolysis and proteolysis, are initially involved, leading to secondary metabolites production responsible for flavor precursors origin (40). As a consequence, ripening time plays an important role in flavor development (41).…”
Section: Discussionmentioning
confidence: 99%
“…MIR and the NIR spectroscopy have been used to analyse cheeses for their authenticity, identification, separation and/ or differentiation, according to the type of processing, composition and/or geographic location, such as Pecorino and Gouda (Andrade et al 2018), Parmigiano (Cevoli et al 2013;Alinovi et al 2019), Butter cheese (Leite et al 2019), Mozzarella (Pax et al 2019), amongst other cheeses from different origins. Cattaneo et al (2008) applied NIR spectroscopy to determine the geographical origin of the Italian Bitto cheese, Sara et al (2018) performed the discrimination and authentication of Buffalo Mozzarella with Protected Designation of Origin (PDO) in Italy, whilst Karoui et al (2005) used the MIR and the NIR spectroscopy to discriminate Emmental cheese from different geographical origins in Europe.…”
Section: Introductionmentioning
confidence: 99%